Ferroelectric origin in one-dimensional undoped ZnO towards high electromechanical response. Issue 4 (7th January 2016) - Ghosh, Moumita; Ghosh, Siddharth; Seibt, Michael; Rao, K. Yellareswara; Peretzki, Patrick; Mohan Rao, G.
Abstract : Ferroelectricity in ZnO is an unlikely physical phenomenon. Here, we show a defect engineering approach of ferroelectricity generation in ZnO nanocrystals. Abstract : Ferroelectricity in ZnO is an unlikely physical phenomenon. Here, we show ferroelectricity in undoped [001] ZnO nanorods due to zinc vacancies. Generation of ferroelectricity in a ZnO nanorod effectively increases its piezoelectricity and turns the ZnO nanorod into an ultrahigh-piezoelectric material. Here using piezoelectric force microscopy (PFM), it is observed that increasing the frequency of the AC excitation electric field decreases the effective d 33 . Subsequently, the existence of a reversible permanent electric dipole is also found from the P–E hysteresis loop of the ZnO nanorods. Under a high resolution transmission electron microscope (HRTEM), we observe a zinc blende stacking in the wurtzite stacking of a single nanorod along the growth axis. The zinc blende nature of this defect is also supported by the X-ray diffraction (XRD) and Raman spectra. The presence of zinc vacancies in this basal stacking fault modulates p–d hybridization of the ZnO nanorod and produces a magnetic moment through the adjacent oxygen ions. This in turn induces a reversible electric dipole in the non-centrosymmetric nanostructure and is responsible for the ultrahigh-piezoelectric response in these undoped ZnO nanorods. We reveal that this defect engineered ZnO can be considered to be in the competitive class of ultrahigh-piezoelectric nanomaterials for energy harvesting and electromechanical device fabrication.